Tesis de la Escuela de Historia, Universidad de Costa Rica 1946-1999. - Román Trigo, Ana Cecilia (Universidad de Costa Rica, 1999)
Tesis de la Escuela de Historia, Universidad de Costa Rica 1946-1999.